Healthy individuals carrying the PCSK9 p.R46L variant and familial hypercholesterolemia patients carrying PCSK9 p.D374Y exhibit lower plasma concentrations of PCSK9. - Humphries, SE; Neely, R; Whittall, R; Troutt, J; Konrad, R; Scartezini, M; Li, K; Cooper, J; Acharya, J; Neil, A (2009)
BACKGROUND: We measured plasma PCSK9 concentrations in healthy men with a PCSK9 (proprotein convertase subtilisin/kexin type 9) loss-of-function variant (p.R46L), in statin-treated patients with a clinical diagnosis of familial hypercholesterolemia (FH) and carrying a PCSK9 gain-of-function mutation (p.D374Y), and in statin-treated patients with FH due to different genetic causes. METHODS: PCSK9 was measured with a previously described ELISA. RESULTS: In 81 healthy middle-aged Caucasian men, the PCSK9 concentration was significantly associated with the concentrations of total cholesterol (r = 0.42; P < 0.0001), LDL cholesterol (r = 0.34; P = 0.01), and triglycerides (r = 0.25; P = 0.02). In p.R46L carriers, mean (SD) concentrations of PCSK9 were 15% lower than in RR individuals [65.5 microg/L (21.6 microg/L) vs 77.5 microg/L (18.2 microg/L); P = 0.03]. In patients with the p.D374Y variant (n = 7), the mean PCSK9 concentration was significantly lower than in the combined group of patients with an LDLR (low density lipoprotein receptor) mutation (n = 25), an APOB [apolipoprotein B (including Ag(x) antigen)] variant encoding p.R3527Q (n = 6), or no detectable mutation (n = 14) [96.4 microg/L (42.5 microg/L) vs 151.6 microg/L (69.6 microg/L); P = 0.02]. Two of the 14 patients with no mutation had PCSK9 concentrations below the mean for p.D374Y carriers; sequencing of the PCSK9 gene and promoter revealed no mutations. Among 409 FH patients, we identified 6 carriers of the promoter variant -287G>A (1.5%), a frequency similar to that (1.0%) previously reported for 2772 healthy men in the UK. In neither group was the -287G>A variant associated with differences in lipid traits. CONCLUSIONS: The loss-of-function p.R46L variant is associated with the expected lower concentrations of circulating PCSK9; the gain-of-function p.D374Y mutation is also associated with lower concentrations, presumably because of the higher affinity of this variant for the LDL receptor and its more rapid clearance. In treated FH patients, a low plasma PCSK9 concentration does not appear to be a useful screening tool for identifying novel PCSK9 mutations.